Berczeli Anzelm Károlyhoz - M. B. Dimt (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1949)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek